Prevailing Nutritional Practices Adopted by Senior Secondary School Students in Delta State, Nigeria - Oghenevwarhe Itagar (EDUCTUM: Journal Research, 2025)
This study investigated the prevailing nutritional practices adopted by Senior Secondary School students in Delta State, Nigeria. The study employed a descriptive survey design using an ex-post facto approach. The population comprised 14,819 students from public secondary schools across the three senatorial districts of Delta State. A sample of 390 students was selected through multistage sampling using Slovin’s formula. Data were collected using a validated questionnaire with a reliability coefficient of 0.81 and analyzed using descriptive statistics and t-test analysis at a 0.05 significance level. The findings revealed that students predominantly engaged in unhealthy nutritional practices, including emotional eating (M = 3.38), consuming large food portions (M = 3.07), frequent snacking (M = 3.06), and meal skipping (M = 2.92). Healthy behaviors such as daily fruit and vegetable consumption (M = 2.28) and regular physical exercise (M = 2.41) were not commonly practiced. Furthermore, the t-test result indicated no significant difference between male and female students regarding nutritional practices (t = 0.20, p = 0.85). The study concludes that unhealthy dietary behaviors are widespread among students regardless of gender, highlighting the need for targeted nutrition education and school-based health intervention programs.